The impact of the health microinsurance M-FUND on the utilization of health services among migrant workers and their dependents in Thailand: a case-control study - König, Andrea; Sappayabanphot, Jarntrah; Liang, Li; Fleßa, Steffen; Winkler, Volker (Journal of migration and health, 2024)
Background - Even though Thailand has launched multiple migrant health policies, migrants still face various barriers in accessing health care. To some extent, these barriers may be reduced by health microinsurance. The M-FUND is a low-cost, not-for-profit health protection scheme for migrant workers in Thailand, created by Dreamlopments Social Enterprise and Foundation to support sustainable access to quality healthcare services for migrants. We aimed to investigate the impact of the M-FUND on utilization of health services. - Methods - Over a period of three months, we conducted quantitative face-to-face interviews with 408 M-FUND members, and 452 age, sex and location matched non-member controls in Tak Province, Thailand. We compared utilization of health services between members and non-members using logistic regression controlling for a number of socio-demographic variables and variables related to migration such as years in Thailand, legal status, etc. - Findings - M-FUND members were more likely to have utilized outpatient services (adjusted odds ratio: 1·74, 95 % confidence interval: 1·24-2·44), inpatient services (2·96, 1.11-7·92), and emergency care (1·89, 0·78-4·56), although the latter was not statistically significant. Members were more likely not to have purchased medicines over-the-counter (1·67, 1·22-2·27) than non-members. Members were also more likely to have utilized any additional specific service during a consultation (2·31, 1·49-3·58) including any type of imaging method (2·62, 1·29-5·29) and blood tests (1·64, 0·99-2·71). There were some differences between men and women, but most were not statistically significant. - Interpretation - The M-FUND health microinsurance was positively associated with the utilization of all major types of health services among migrant workers and their dependents in Thailand. For migrants, particularly vulnerable migrant workers and their dependents, the M-FUND appears to be a good approach to reducing barriers to health care. This study of the impact of health microinsurance for migrants provides important information for policy and program planners in the field of migrant health. However, more research is needed on health microinsurance schemes for migrants in different settings and for other underserved communities as well as the sex-specific impact on health service utilization.